Monetized home sharing: the tourist experience and its effects on perceived authenticity, destination attachment and loyalty - Souza, Luís Henrique de (2020)
The emergence of the shared peer-to-peer accommodation (SP2PA) has attracted the attention of practitioners and academics, given this new business model’s increasing popularity amongst travellers. It is therefore suggested that this type of accommodation can offer a differentiated, eventually more authentic, experience to its guests, introducing new values and meanings to the hospitality provided at destinations. To sustain this argument, it is important to enhance the understanding of guest experiences while staying in such a SP2PA, while also the impact of these new tourist behaviour patterns on destinations is worthwhile exploring. Taking into account the relevance of understanding the tourist experience associated with the SP2PA, this study aims to gain theoretical and empirical understanding of the SP2PA guest experience by proposing and testing a theoretical model that estimates the relationships between the dimensions of the tourist experience (the SP2PA guest experience) and the constructs of ‘destination attachment’, ‘perception of authenticity’, ‘destination attitudinal loyalty’ and ‘SP2PA attitudinal loyalty’. To achieve this goal, two complementary methodology stages were undertaken: (i) an ‘exploratory qualitative approach’ by conducting focus group discussions and passive netnography; and (ii) a ‘quantitative approach’ by applying a survey to a convenience sample of SP2PA guests. Statistical analysis of data used descriptive and inferential methods, with the Partial Least Squares (PLSSEM) as the main method for testing the hypotheses. A total of 409 valid responses were used to test the proposed conceptual model. Findings confirm the ‘aesthetic’, ‘escape’, ‘entertainment’, ‘educative’, ‘affective’, ‘social interaction’, and ‘sharing experience’ dimensions as appropriated dimensions to analyse the SP2PA guest experience. Amongst these dimensions, the ‘educative’, ‘social interaction’, ‘aesthetics’, ‘sharing’, and ‘affective’ are, in this order, the dimensions that most influence the SP2PA guest experience. Regarding the influence of the SP2PA guest experience on the tourist experience outcomes, this study demonstrates that this experience positively influences the ‘perception of destination authenticity’ and ‘destination attachment’ formation. In turn, destination attachment mediates the relationship between the ‘SP2PA guest experience’ and ‘destination loyalty’, while the SP2PA guest experience predicts the ‘SP2PA attitudinal loyalty’. Besides, the ‘perception of authenticity’ positively influences ‘destination attachment’ formation and ‘SP2PA attitudinal loyalty’. The results contribute to the tourist experience theory by providing an empirically-based insight into its dimensionality in the hospitality sharing economy context. This study also provides an analytical framework to understand the effects of the SP2PA guest experience on constructs such as the perception of authenticity, destination attachment and tourist loyalty. Furthermore, results may help design management strategies for both SP2PA platforms and SP2PA hosts to develop and implement an experience-oriented service strategy in order to achieve a memorable experience for SP2PA guests and create positive future behavioural intentions. Limitations of the study and suggestions for further research complete the picture.